The Use of Bacillus spp. as Probiotic in Feed on Snake-head Fish (Channa striata) Culture - Senasri, Naiyana; Simawan, Jitra; Kumla, Sugunya (Journal of Mahanakorn Veterinary Medicine, 2018)
The experiment was conducted to determine the optimum level of concentration of probiotic supplement, Bacillus spp., in feed on growth rate and survival rate of snake-head fish (Channa striata). Snake-head fishes with the range of initial weights during 2.50-3.50 g were raised in 250-liter fiberglass tanks, 3 replications per treatment. Bacillus spp. (3.0×107 CFU/g) in different levels as 0, 2, 4 and 6 g were added to 1 kg of commercial diet to feed fish and then he fished were offered he diet for 60 days. The result showed that using 6 g/kg feed of Bacillus spp. was the best treatment for increasing the average of weight gain, length gain and growth rate of the studied fishes as 6.62±0.44 g/fish, 3.13±0.45 cm/fish and 2.06±0.02 %/day, respectively, with a statistically significant difference (P<0.05). However, it was not found the difference of the survival rate. The result of water quality analysis exhibited no any statistically significant difference among the studied groups (P>0.05). In conclusion, using 6 g/kg feed of Bacillus spp. as feed additive on snake-head fish culture was the best choice for increasing weight gain, length gain, and growth rate of snake-head fishes.